TOURISM COMMUNICATION BASED ON CULTURE, RELIGION AND LOCAL WISDOM OF KUANTAN SENGINGI - Ismandianto Ismandianto; Muchid Muchid; Prima Wahyudi (Sosiohumaniora, 2023)
Tourism competition between regions has recently become increasingly competitive, to be able to compete, an effective strategy is needed to develop the potential and uniqueness of the region to be competitive. For this reason, the development of tourist destinations must be more innovative so that tourists who come are willing to repeat their visits in these tourist areas. The main problem that arises related to tourism in the region at this time is how to increase regional competitiveness so that its potential can be exploited to the fullest. This study aims to determine the tourism communication strategy in developing tourism potential in Kuantan Singingi Regency. This research method is using a qualitative descriptive approach using a constructivist paradigm. Data collection techniques were carried out by observation, interviews, and documentation. To test the validity of the data in the field, a credibility test was conducted.  The results of tourism communication research are the process of delivering image messages that involve the role of stakeholders, both internal and external. The right strategy to be carried out by the Kuantan Singingi Regency government in developing regional tourism potential, elaborating brand image and brand identity, will be able to develop the potential and uniqueness of the region to become a tourism strength. The pattern of communication strategies between local governments and communities lacks synergy, with local tourism communities and human resources that do not have expertise in tourism.